Navigating Employment Pathways: A Microeconomic Examination of Job Search Strategies and Their Impact - Benhamed, Adel (Journal of Posthumanism, 2025)
The current paper aims to determine and evaluate the mechanisms that facilitate the transition of young graduates into the Tunisian labor market. In particular, the study examines the multitude of insertion modes of young graduates to study the efficiency of accessing the first job.We employ a micro econometric analysis to examine the transition modes chosen by job candidates. Our approach considers whether candidates know or disregard the endogenous selection rules governing their entry methods. Given the qualitative nature of our dependent variable, we utilize various econometric models designed for discrete variable estimation, including: Trivariate Probit model and Ordered Probit model. These models allow us to capture the nuanced dynamics of job market entry strategies and their outcomes, providing insights into the complex process of labor market integration for young Tunisian graduates.